Perspektif Akuntansi Lingkungan: Suatu Tinjauan Teoritis Mengenai Dampak Isu Lingkungan Terhadap Akuntansi - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1998)
ABSTRACT In the past two decades, concerns regarding environmental degradation, pollution, resource depletion, population growth, and destruction of wildlife and wilderness have become more widespread. Today, current accounting practices suffer from two fatal flaws when it comes to acknowledging the interdependence with resources. First, we cannot account for the full cost of production, including the costs of consuming essential natural resources because they often have no assigned monetary costs. Second, accounting rules penalize, rather than encourage, the environmentally responsible corporation. Accounting lacks a vehicle for recording "green assets" and monitoring their use. It may be argued that the accounting principles underlying GAAP are need some updating to bring them into line with current social options. Environmental cost assessment systems can help improve the decisions regarding: product mix decisions, choosing manufacturing inputs, assessing pollution prevention projects, evaluating waste management options, comparing environmental cost across facilities, and pricing products. To reach these goals there basically four methods costs: adapt the conventional accounting system, use full cost accounting, use an ABC system or use total cost assessment. This paper attempts to discuss the impacts of environmental issues on accounting